Binge Eating and Compulsive Buying During Cabergoline Treatment for Prolactinoma: A Case Report - Correa e Castro, Ana Carolina; de Araujo, Andressa Alexandre; Botelho, Mariana Coelho; Nascimento, João Bosco; de Souza, Rafaela Marchon; Gadelha, Monica Roberto; Nardi, Antonio E.; Violante, Alice Helena Dutra (Frontiers in Psychiatry, 2022)
Prolactinomas are the most prevalent functional pituitary adenomas. They are usually treated clinically with dopamine agonists. The most widely used and suitable drug is cabergoline (CAB), a specific D2 dopamine agonists. Patients in prolactinoma treatment with CAB commonly report physical side effects, but aberrant behavioral changes such as increased impulsivity have also been reported recently. We report the case of a 47-year-old Brazilian woman with prolactinoma that developed compulsive buying, binge eating, and hypersexuality after four years of CAB treatment. In her psychiatric evaluation, the patient scored high levels on the following scales: Compulsive Buying Scale (CBS), Binge Eating Scale (BES), and Barratt Impulsiveness Scale-11 (BIS11). She also reported financial problems and weight gain in addition to her social and clinical problems. Impulsivity disorders may appear with the use of cabergoline and other dopamine agonists. We suggest that more observational studies with a large patient samples and specific regular psychiatric evaluations during treatment are necessary for patients in use of CAB, especially those treated for several years.